Precarious Values and Mundane Innovations: The Diffusion of Enrollment Management in U.S. Higher Education 1970-2005 - Ventresca, M; Kraatz, M; Deng, L (2010)
Drawing primarily from Selznick's institutionalism, we make a general case for renewed attention to the "mundane administrative arrangements" that underlie the organizational capacity for value realization and a particular case for the study of value-subverting management innovations. An empirical study of "enrollment management" in liberal arts colleges reveals this ostensibly innocuous innovation's value-undermining effects and identifies the organizational and environmental factors that have made these venerable organizations more or less susceptible to its adoption.